Service aquality and measurement of service quality by servqual: a study on Kyrgyzstan airlines customers - Alymbaev, Beknazar (My University, 2002)
The objectives of this research were to investigate the service quality expectations and service quality perceptions belonging to the passengers of Kyrgyzstan Airlines. In order to specify the expectations and service quality perceptions of the Kyrgyzstan Airlines' passengers SERVQUAL model is used. This study includes the review of literature concerning service and service quality. And also SERVQUAL model evaluated in details, especially four Gaps of service quality and closing those Gaps. The findings of the study shows that generally the satisfaction level of passengers are low than their expectations. For customers of Kyrgyzstan Airlines it is founded out that most important dimension of service quality is reliability. Kyrgyzstan Airlines should immediately take into account to improve their quality of service in order to be competitive with other foreign airlines.

Tezin amacı, Kırgızistan Hava Yolları yolcularının hizmet beklentilerini ve servis kalitesi konusundaki algılarını araştırmak olarak belirlenmiştir. Kırgızistan Hava Yolları yolcularının hizmet beklentileri ve hizmet kalitesi konusundaki algılamalarının belirlenmesi amacıyla SERVQUAL modeli uygulanmıştır. Çalışma hizmet ve hizmet kalitesi konusundaki literatürü içermektedir. Özellikle SERVQUAL modeli ve hizmet kalitesindeki boşluklar ve boşlukların doldurulmaması incelenmiştir. Araştırmanın bulgularına göre, Kırgızistan Hava Yolları yolcuları servisten aldıkları tatmin beklentilerin altında kalmaktadır. Kırgızistan Hava Yolları yolcuları için en önemli hizmet kalitesi boyutunun güvenirlik olduğu tespit edilmiştir. Kırgızistan Hava Yolları diğer yabancı hava yolları ile rekabet edebilmek için hizmet kalitesini acil iyileştirmesi gerekmektedir.
Keywords: Hava Taşımacılığı